2021
DOI: 10.1186/s12877-021-02649-1
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ thoughts on their falls in a rehabilitation hospital: a qualitative study of patients with stroke

Abstract: Background Patients with stroke in rehabilitation wards are at an increased risk of falling. Although patients’ participation in establishing medical safety is considered crucial, there is limited evidence on their perspectives of falls. This study aims to comprehensively elucidate the subjective falling experience of patients with stroke who have been admitted to rehabilitation wards. Methods Twenty-three consecutive patients with stroke (44 to 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…So they become involuntarily nervous and concentrated when challenged with complex tasks. The fear of falling may massively increase their focus to cope with unfamiliar or unpredictable situations (Aihara et al, 2021 ). Eventually the patient exhibits a cautious gait and an increase in the control of walking (Rosén et al, 2005 ; Schinkel-Ivy et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…So they become involuntarily nervous and concentrated when challenged with complex tasks. The fear of falling may massively increase their focus to cope with unfamiliar or unpredictable situations (Aihara et al, 2021 ). Eventually the patient exhibits a cautious gait and an increase in the control of walking (Rosén et al, 2005 ; Schinkel-Ivy et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that patients with stroke in the domestic LS group experienced more falls than those in the bedridden and community groups. One possible explanation is that patients in domestic environments have more opportunities to participate in daily activities than bedridden patients, such as toileting, dressing, showering, using stairs, and turning 3. Walking and transfers were the most frequent activities at the time of falling 23.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that patients in domestic environments have more opportunities to participate in daily activities than bedridden patients, such as toileting, dressing, showering, using stairs, and turning. 3 Walking and transfers were the most frequent activities at the time of falling. 23 Furthermore, domestic patients are more likely to have functional disorders than community patients, such as sensory impairment, deficiency of balance, and inattention to details and obstacles of surroundings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for falls in patients with stroke are known to be multifactorial and include difficulties with balance, neglect, and requiring assistance for activities of daily living (Campbell & Matthews, 2010; Denissen et al, 2019). The increased activity of patients as they undergo therapy to regain functional independence is suggested as a contributing factor to the high fall rates in inpatient rehabilitation stroke populations (Aihara et al, 2021; Suzuki et al, 2005; Sze et al, 2001). Hospital falls potentially result in a range of serious and preventable adverse consequences to both the patient and the health service, including injury, loss of functional capacity, increased length of stay, and cost of care (Constantinou & Spencer, 2020; K.…”
Section: Introductionmentioning
confidence: 99%